2020
DOI: 10.1002/mp.14477
|View full text |Cite
|
Sign up to set email alerts
|

3D tumor detection in automated breast ultrasound using deep convolutional neural network

Abstract: Purpose Automated breast ultrasound (ABUS) has drawn attention in breast disease detection and diagnosis applications. Reviewing hundreds of slices produced by ABUS is time‐consuming. In this paper, a tumor detection method for ABUS image based on convolutional neural network is proposed. Methods First, integrating multitask learning with YOLOv3, an improved YOLOv3 detection network is designed to detect tumor candidate in two‐dimensional (2D) slices. Two‐dimensional detection separately treats each slice, lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…2 The need for monitor unit verification programs was identified early in the adoption of IMRT treatment planning and delivery techniques. 3 Several different types of programs were developed ranging from confirmation of dose at a single point in a simple phantom geometry to calculation of dose at a single point while taking patient anatomy and geometry into consideration. While these programs have been in use for some time, guidance was lacking in how to commission such technologies as well as their role as part of an IMRT QA program as was noted in the ASTRO white paper entitled "Safety Considerations for IMRT".…”
Section: Statement Of the Problem And Tg Chargesmentioning
confidence: 99%
“…2 The need for monitor unit verification programs was identified early in the adoption of IMRT treatment planning and delivery techniques. 3 Several different types of programs were developed ranging from confirmation of dose at a single point in a simple phantom geometry to calculation of dose at a single point while taking patient anatomy and geometry into consideration. While these programs have been in use for some time, guidance was lacking in how to commission such technologies as well as their role as part of an IMRT QA program as was noted in the ASTRO white paper entitled "Safety Considerations for IMRT".…”
Section: Statement Of the Problem And Tg Chargesmentioning
confidence: 99%
“…The CNN-based methods have made significant achievements in tumor detection 3,4 and tumor segmentation. [5][6][7][8] In related studies, the fully convolutional network (FCN) 7 and U-Net 8 are two representative approaches which have strong competitiveness compared with the existing brain tumor MRI image segmentation algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…3. May indicates a statement that is likely (or probably) to be correct but the task group does not make any recommendations.…”
mentioning
confidence: 99%
“…As the most popular machine learning method, deep learning (DL) has gained a good reputation in computer vision and pattern recognition. In the medical field, many researchers have successfully applied DL to breast cancer detection 9 13 . Cao et al 14 comprehensively compared five object detection networks based on deep learning (Fast R-CNN 15 , Faster R-CNN 16 , you only look once (YOLO) 17 , YOLO V3 18 , and single shot multibox detector (SSD) 19 ), and demonstrated that SSD achieved the best performance in terms of precision and recall.…”
Section: Introductionmentioning
confidence: 99%